2000
DOI: 10.1088/0953-4075/33/14/309
|View full text |Cite
|
Sign up to set email alerts
|

Thermalization times of positrons in molecular gases

Abstract: The time taken for positrons to reach thermal equilibrium in a number of simple molecular gases has been estimated using the gas mixture technique devised by Paul and Leung (Paul D A L and Leung C Y Can. J. Phys. 46 2779-88). Times below 100 ps Amagat have been found for a number of species, suggesting their use as efficient coolers for rapid-cycle positron traps and accumulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 27 publications
3
19
0
Order By: Relevance
“…Use of the RW during accumulation (see below) requires the presence of an extra cooling gas, to counteract the positron heating caused by the rotating electric field. In our case SF 6 is used, as this is known to be an efficient positron cooler (e.g., [35]).…”
Section: Apparatusmentioning
confidence: 99%
“…Use of the RW during accumulation (see below) requires the presence of an extra cooling gas, to counteract the positron heating caused by the rotating electric field. In our case SF 6 is used, as this is known to be an efficient positron cooler (e.g., [35]).…”
Section: Apparatusmentioning
confidence: 99%
“…However, it has also been known for many years, again from positron lifetime measurements, that, among the molecular gases, nitrogen is the poorest positron cooler, with the lowest density-normalized cooling rate or the longest thermalization time [37][38][39][40]. Thus, if a rapid cooling is required, which is the case here when the rotating wall is used, a further gas must be inserted into the system.…”
Section: Commentarymentioning
confidence: 99%
“…Thus, if a rapid cooling is required, which is the case here when the rotating wall is used, a further gas must be inserted into the system. Investigations have revealed that several gases have thermalization times about 100 times shorter than N 2 [40], such that addition of small quantities of these to the lowest potential region of the accumulator will promote positron cooling. SF 6 is one such gas, and this has been used in this study and in previous work [14,22,26].…”
Section: Commentarymentioning
confidence: 99%
“…The data reported in Refs. [18][19][20][21] are also presented in Tables 2 and 3. The typical SDTs are about three orders higher than for the times in solid state presented above.…”
Section: Sdt In Gasesmentioning
confidence: 99%
“…It is difficult to evaluate scattering cross sections for positrons of energies less than 1 keV, where the quantum theory with the Born approximation implanted to GEANT4 simulations is no longer valid. The authors [18,19,22] proposed to separate three energetic regions in the slowing down process: (i) for energy above 1 keV, (ii) below 1 keV but above the excited level of the gas molecule, (iii) and the region below the excited level down to the thermal energy. All regions include the significant contribution to the SDT.…”
Section: Sdt In Gasesmentioning
confidence: 99%